Symbiosis disruption in the olive fruit fly, Bactrocera oleae (Rossi), as a potential tool for sustainable control. Issue 9 (26th May 2020) - Sinno, Martina; Bézier, Annie; Vinale, Francesco; Giron, David; Laudonia, Stefania; Garonna, Antonio P; Pennacchio, Francesco
Abstract: BACKGROUND: The olive fruit fly Bactrocera oleae (Rossi) (OLF) is a major agricultural pest, whose control primarily relies on the use of chemical insecticides. Therefore, development of sustainable control strategies is highly desirable. The primary endosymbiotic bacterium of OLF, ' Candidatus Erwinia dacicola', is essential for successful larval development in unripe olive fruits. Therefore, targeting this endosymbiont with antimicrobial compounds may result in OLF fitness reduction and may exert control on natural populations of OLF. RESULTS: Here, we evaluate the impact of compounds with antimicrobial activity on the OLF endosymbiont. Copper oxychloride (CO) and the fungal metabolite viridiol (Vi), produced by Trichoderma spp ., were used. Laboratory bioassays were carried out to assess the effect of oral administration of these compounds on OLF fitness and molecular analyses (quantitative polymerase chain reaction) were conducted to measure the load of OLF‐associated microorganisms in treated flies. CO and Vi were both able to disrupt the symbiotic association between OLF and its symbiotic bacteria, determining a significant reduction in the endosymbiont and gut microbiota load as well as a decrease in OLF fitness. CO had a direct negative effect on OLF adults. Conversely, exposure to Vi significantly undermined larval development of the treated female's progeny but did not show any toxicity in OLF adults. CONCLUSIONS: These results provide new insights into the symbiotic control of OLF and pave the way for the development of more sustainable strategies of pest control based on the use of natural compounds with antimicrobial activity. © 2020 Society of Chemical Industry Abstract : Antimicrobial compound produced by Trichoderma spp. and copper oxychloride are able to disrupt bacterial symbiosis in Bactrocera oleae, driving a significant reduction in olive fruit fly fitness.